International human rights, social policy and global development : critical perspectives / edited by Gerard McCann and Félim Ó hAdhmaill ; forword by Albie Sachs. - McCann, Gerard; Ó hAdhmaill, Félim; Sachs, Albie, 1935- (Policy Press, 2020)
With international human rights under challenge, this book represents a comprehensive critique that adds a social policy perspective to recent political and legalistic analysis. Expert contributors draw on local and global examples to review constructs of universal rights and their impact on social policy and human welfare. With thorough analysis of their strengths, weaknesses and enforcement, it sets out their role in domestic and geopolitical affairs. Including a forward by Albie Sachs, this book presents an honest appraisal of both the concepts of international human rights and their realities. It will engage those with an interest in social policy, ethics, politics, international relations, civil society organisations and human rights-based approaches to campaigning and policy development.